Evaluation of the Oxiris Membrane in Cardiogenic Shock Requiring Extracorporeal Membrane Oxygenation Support: Study Protocol for a Single Center, Single-Blind, Randomized Controlled Trial - Andrei, Stefan; Nguyen, Maxime; Berthoud, Vivien; Morgant, Marie-Catherine; Bouhemad, Belaid; Guinot, Pierre-Grégoire; , The ECMORIX Study Group; Martin, Audrey; Radhouani, Mohamed; Constandache, Tiberiu; Grosjean, Sandrine; Voizeux, Pierre; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is the rescue treatment proposed to patients with refractory cardiogenic shock. The VA-ECMO implantation promotes inflammation and ischemia-reperfusion injuries through the VA-ECMO flow, causing digestive mucosa barrier disrupture and inducing translocation of bacterial wall components—Lipopolysaccharides (LPS) with further inflammation and circulatory impairment. LPS is a well-studied surrogate indicator of bacterial translocation. Oxiris membrane is a promising and well-tolerated device that can specifically remove LPS. The main study aim is to compare the LPS elimination capacity of Oxiris membrane vs. a non-absorbant classical renal replacement (RRT) membrane in patients with cardiogenic shock requiring VA-ECMO. Methods: ECMORIX is a randomized, prospective, single-center, single-blind, parallel-group, controlled study. It compares the treatment with Oxiris membrane vs. the standard continuous renal replacement therapy care in patients with cardiogenic shock support by peripheral VA-ECMO. Forty patients will be enrolled in both treatment groups. The primary endpoint is the value of LPS serum levels after 24 h of treatment. LPS serum levels will be monitored during the first 72 h of treatment, as clinical and cardiac ultrasound parameters, biological markers of inflammation and 30-day mortality. Discussion: Oxiris membrane appears to be beneficial in controlling the VA-ECMO-induced ischemia-reperfusion inflammation by LPS removal. ECMORIX results will be of major importance in the management of severe cases requiring VA-ECMO and will bring pathophysiological insights about the LPS role in this context. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04886180.